2016
DOI: 10.1183/13993003.01129-2016
|View full text |Cite
|
Sign up to set email alerts
|

Severe asthma exists despite suppressed tissue inflammation: findings of the U-BIOPRED study

Abstract: on behalf of the U-BIOPRED Study Group 16ABSTRACT The U-BIOPRED study is a multicentre European study aimed at a better understanding of severe asthma. It included three steroid-treated adult asthma groups (severe nonsmokers (SAn group), severe current/ex-smokers (SAs/ex group) and those with mild-moderate disease (MMA group)) and healthy controls (HC group). The aim of this cross-sectional, bronchoscopy substudy was to compare bronchial immunopathology between these groups.In 158 participants, bronchial biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 40 publications
12
43
0
Order By: Relevance
“…Thus, in treatment-resistant severe asthma there appears to be an effective steroid response in central airways, which is less evident in peripheral airways where the IL-13 disease signature persists (Fig 5). This would be consistent with recently reported central airway biopsy findings in severe asthma [29]. …”
Section: Discussionsupporting
confidence: 94%
“…Thus, in treatment-resistant severe asthma there appears to be an effective steroid response in central airways, which is less evident in peripheral airways where the IL-13 disease signature persists (Fig 5). This would be consistent with recently reported central airway biopsy findings in severe asthma [29]. …”
Section: Discussionsupporting
confidence: 94%
“…Cell counts were performed in a blinded fashion and expressed as number of positive cells/mm 2 . These results have already been reported …”
Section: Methodssupporting
confidence: 87%
“…Because the comparison of asthmatic to normal controls did not yield any satisfactory clinical profiles, we next focused on the transcriptomic differences in bronchial biopsies between eosinophil‐high and eosinophil‐low patients. To this end, the K‐mean clustering method was applied, which yielded four homogeneous mucosal eosinophil clusters (low, medium‐low, medium‐high, and high; Figure A), as determined by the within‐group sum of squares, using the eosinophil counts in bronchial biopsies that have been previously reported in this cohort (Figure B). The low and medium‐low clusters were further aggregated as the low mucosal eosinophil (LE) group (n = 48), and the medium‐high and high clusters as the high mucosal eosinophil (HE) group (n = 33).…”
Section: Resultsmentioning
confidence: 99%
“…3 This is the biggest study of its kind and revealed unexpected data. There were fewer mast cells in the submucosa of the asthmatics than with the healthy controls.…”
Section: Q: How Can the Definition Of Asthma Phenotypes Help In Diseamentioning
confidence: 99%